Multidisciplinary strategy to reduce errors with the use of medical gases - María Sanjurjo Sáez; Ana Herranz Alonso; Alicia Díaz-Redondo; Sara Ibáñez-García; Miguel Ángel Amor-García (Elsevier, 2018)
Objective: Lack of awareness of the risks associated with the use of medical gases amongst health professionals and health organizations is concerning. The objective of this study is to redefine the use process of medical gases in a hospital setting. Method: A sentinel event took place in a clinical unit, the incorrect administration of a medical gas to an inpatient. A multidisciplinary causeroot analysis of the sentinel event was carried out. Different improvement points were identified for each error detected and so we defined a good strategy to ensure the safe use of these drugs. Results: 9 errors were identified and the following improvement actions were defined: storage (gases of clinical use were separated from those of industrial use and proper identification signs were placed), prescription (6 protocols were included in the hospital´s Computerized Physician Order Entry software), validation (pharmacist validation of the prescription to ensure appropriate use of these), dispensation (a new protocol for medical gases dispensation and transportation was designed and implemented) and administration (information on the pressure gauges used for each type of gas was collected and reviewed). 72 Signs with recommendations for medical gases identification and administration were placed in all the clinical units. Specific training on the safe use of medical gases and general safety training was imparted. Conclusions: The implementation of a process that integrates all phases of use of medical gases and applies to all professionals involved is presented here as a strategy to increase safety in the use of these medicines.